Perancangan Interior Museum Songket di Lombok - Agustina T, Melina (Intra, 2013)
Indonesias remarkable cultural good can be typical of Indonesias identity. One example of a work of art that is Indonesia songket. Songket is a type of woven cloth which can be classed in the family woven brocades. Hand-woven Songket with threads of gold and silver and are generally worn on formal occasions. Lombok is one of the areas that produce woven songket. Kain songket sasak are already known by the beauty and subtlety of his mantle motif. The design emphasizes the aspect of informative, educative and recreative which provided the lobby area, cafe, souvenir shop, Gallery, workshop, library, maintenance and grounds of natural dyes. The concept used is The Beauty of Songket where the intended design is able to show the beauty of lombok songket cloth by using one of the motifs of songket Lombok as motif in the application layout, materials, colors, and so on. The application form used the balanced forms, geometric (rigid) and game lines.